First reports of Pseudo‐nitzschia micropora and P. hasleana (Bacillariaceae) from the Southern Hemisphere: Morphological, molecular and toxicological characterization. Issue 3 (3rd June 2013) - Ajani, Penelope; Murray, Shauna; Hallegraeff, Gustaaf; Brett, Steve; Armand, Leanne
Summary: Pseudo‐nitzschia H. Peragallo is a marine diatom genus found worldwide in polar, temperate, subtropical and tropical waters. It includes toxigenic representatives that produce domoic acid (DA), a neurotoxin responsible for Amnesic Shellfish Poisoning. In this study we characterized two species of Pseudo‐nitzschia collected from Port Stephens and the Hawkesbury River (south eastern Australia) previously unreported from Australian waters. Clonal isolates were sub‐sampled for (i) light and transmission electron microscopy; (ii) DNA sequencing, based on the nuclear‐encoded partial large subunit ribosomal RNA gene and internal transcribed spacer (ITS)‐ITS1, 5.8S and ITS2 rDNA regions and, (iii) DA production as measured by liquid chromatography‐mass spectrometry. Morphological and molecular data unambiguously revealed the species to be Pseudo‐nitzschia micropora Priisholm, Moestrup & Lundholm (Port Stephens) and Pseudo‐nitzschia hasleana Lundholm (Hawkesbury River). This is the first report of the occurrence of these species from the Southern Hemisphere and the first report of P. micropora in warm‐temperate waters. Cultures of P. micropora, tested for DA production for the first time, proved to be non‐toxic. Similarly, no detectable toxin concentrations were observed for P. hasleana . Species resolution and knowledge on the toxicity of local Pseudo‐nitzschia species has important implications for harmful algal bloom monitoring and management.